Pengaruh pelatihan terhadap peningkatan pengetahuan dan keterampilan penjamah makanan dalam penyelenggaraan makanan - Elfiana Elfiana; Suryana Suryana (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: The organization of hospital meals aims to help and accelerate the patient's healing process, shorten the length of treatment and save on medical costs. The quality and taste of the food to be served can satisfy consumers or customers and the cost of providing services can be reduced to the lowest possible level and does not reduce the quality of service.Objectives: To find out the effect of training on increasing the knowledge of food handlers.Methods: The study used a Quasi-Experiment design with a one group pre-test and post-test approach. A sample of 13 handlers was taken according to the total population. This research was conducted at Kindergarten II Iskandar Muda Hospital, Banda Aceh, from February to March 2019. The research variable was the effect of training on increasing the knowledge and skills of food handlers in food management. Data analysis using T-test dependent.Results: Before being given food management training, the average knowledge was 24.77 and skills were 36.00. Meanwhile, after being given training, the average knowledge increased to 92.77 and skills to 113.69. Statistical results showed that the effect of training on increasing knowledge (p= 0.000) and also the skills of food handlers increased significantly (p= 0.000).Conclusion: The training that has been given to food handlers on food handling can improve knowledge for the better and improve the skills of handlers in carrying out food handling at the hospital.